Three-dimensional quantitative temporomandibular joint changes in skeletal class I malocclusion treated with extraction and non-extraction protocols: a comparative study of fixed orthodontic appliances and clear aligners - Majedh Abdo Ali Al-Somairi; Bowen Zheng; Xaiofeng Yang; Yongxin Zhang; Maged S. Alhammadi; Hao xu; Najah Alhashimi; Bushra Sufyan Almaqrami; Naseem Ali Al –Worafi; Enas Senan Alyafrusee; Barakat Al-Tayar; Yi Liu (Progress in Orthodontics)
Abstract Objective This study aimed to evaluate the positional and morphological changes in the temporomandibular joint (TMJ) in adult patients with skeletal Class I malocclusion treated with fixed orthodontic appliances (FAs) and clear aligners (CAs), both with and without premolar extractions. Methods This retrospective study involved 120 adult patients divided into non-extraction and extraction groups, each further subdivided equally into those treated with FAs and CAs. Cone beam computed tomography (CBCT) was used to assess the TMJ measurements before (T0) and after treatment (T1). Statistical analyses were conducted to compare the mean changes in intra- and inter-groups. A significance level of p ≤ 0.05 was considered. Results In the non-extraction group, specifically in FAs, significant increases were observed in TMJ parameters; anteroposterior condylar position (APCP) and mediolateral condylar inclination (MCI). Conversely, significant decreases were noted in vertical condylar position (VCP) and vertical condylar inclination (VCI). In the extraction group, significant increases were noted in APCP and anterior joint space (AJS), while posterior joint space (PJS) and anteroposterior condylar joint position (APCJP) decreased. For inter-group comparisons, the extraction group showed significant increases in APCP in FAs compared to CAs, and a significant decrease in APCJP in FAs compared to CAs. Conclusion FAs significantly impact condylar positions and joint spaces, especially in extraction cases. Monitoring TMJ parameters during orthodontic treatment is crucial to ensure positive outcomes and prevent TMJ disorders (TMDs). These findings may guide the selection of orthodontic appliances based on individual malocclusion characteristics.